Gatewatching and news curation journalism, social media, and the public sphere - Bruns, Axel 1970- (Digital formations, 2018)
Gatewatching and News Curation: Journalism, Social Media, and the Public Sphere documents an emerging news media environment that is characterised by a more and more networked and social structure.